Field evidence for manipulation of mosquito host selection by the human malaria parasite, Plasmodium falciparum - Vantaux, Amélie; Yao, Franck; Hien, Domonbabele FdS; Guissou, Edwige; Yameogo, Bienvenue K.; Gouagna, Louis-Clément; Fontenille, Didier; Renaud, François; Simard, Frédéric; Constantini, Carlo; Thomas, Fréderic; Mouline, Karine; et al. (Peer Community Journal, 2021)
Whether the malaria parasite Plasmodium falciparum can manipulate mosquito host choice in ways that enhance parasite transmission toward humans is unknown. We assessed the influence of P. falciparum on the blood-feeding behaviour of three of its major vectors (Anopheles coluzzii, An. gambiae and An. arabiensis) in Burkina Faso. Host preference assays using odour-baited traps revealed no effect of infection on mosquito long-range anthropophily. However, the identification of the blood meal origin of mosquitoes showed that females carrying sporozoites, the mature transmissible stage of the parasite, displayed a 24% increase in anthropophagy compared to both females harbouring oocysts, the parasite immature stage, and uninfected individuals. Using a mathematical model, we further showed that this increased anthropophagy in infectious females resulted in a 250% increase in parasite transmission potential, everything else being equal. This important epidemiological consequence highlights the importance of vector control tools targeting infectious females.